Rufinus’ Bloody Pagan Tyrants - Hanaghan, M. P. (Vigiliae Christianae, 2021)
Abstract This article analyses how Rufinus alters and then extends Eusebius’ church history to draw a narrative continuum of pagan idolatry, tyranny and blood sacrifice across the fourth century. It begins with a taxonomy that illustrates the various ways that Rufinus’ text differs from Eusebius’ and then analyses how Rufinus enhances the levels of cruelty and bloody carnage in his Eusebian source, especially with regards to the tyrannical behaviour of the pagan emperors Maximinus, Maxentius, and Licinius. Lastly, it turns to Rufinus’ account of Eugenius’ uprising and the destruction of the temple of Serapis and shows how Rufinus’ repeated criticism of pagan imperial persecution acts to justify Theodosius’ actions.